2014
DOI: 10.1016/j.ijid.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin and interferon therapy in patients infected with the Middle East respiratory syndrome coronavirus: an observational study

Abstract: While ribavirin and interferon may be effective in some patients, our practical experience suggests that critically ill patients with multiple comorbidities who are diagnosed late in the course of their illness may not benefit from combination antiviral therapy as preclinical data suggest. There is clearly an urgent need for a novel effective antiviral therapy for this emerging global threat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
324
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(341 citation statements)
references
References 20 publications
5
324
2
7
Order By: Relevance
“…A study in rhesus macaques found that a combination of interferon-α2b and ribavirin was associated with a reduction in MERSCoV replication and improved outcome [45]. Clinical studies on combined ribavirin and interferon showed inconsistent results [46]. Convalescent sera from patients who have recovered may be useful.…”
Section: Specific Therapiesmentioning
confidence: 99%
“…A study in rhesus macaques found that a combination of interferon-α2b and ribavirin was associated with a reduction in MERSCoV replication and improved outcome [45]. Clinical studies on combined ribavirin and interferon showed inconsistent results [46]. Convalescent sera from patients who have recovered may be useful.…”
Section: Specific Therapiesmentioning
confidence: 99%
“…The use of interferon and ribavirin was tried in five patients with MERS-CoV infection. The median time from admission to therapy with these two agents was 19 days, and thus any benefit effect might have not been evident [76]. A larger number of 20 patients received ribavirin and interferon treatment at a median of 3 days [77].…”
Section: Currently Available Antiviral Agents and Vaccinesmentioning
confidence: 99%
“…In a recent observational study of five MERS-CoV patients treated with a combination of interferon and ribavirin, the median time from admission to therapy was 19 (range 10-22) days. In that study, none of the patients responded to the supportive or therapeutic interventions and all died of their illness [34]. It was concluded that critically ill patients with multiple comorbidities who were diagnosed late in the course of their illness may not benefit from combination antiviral therapy [34].…”
mentioning
confidence: 90%